2022
DOI: 10.1186/s12935-021-02433-6
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 promotes lung adenocarcinoma tumor growth and inhibits ferroptosis by stabilizing SLC7A11 m6A modification

Abstract: Background N6-methyladenosine (m6A) has emerged as a significant regulator of the progress of various cancers. However, its role in lung adenocarcinoma (LUAD) remains unclear. Here, we explored the biological function and underlying mechanism of methyltransferase-like 3 (METTL3), the main catalyst of m6A, in LUAD progression. Methods The expression of m6A, METTL3, YTHDF1 and SLC7A11 were detected by immunochemistry or/and online datasets in LUAD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 52 publications
3
60
0
Order By: Relevance
“…Consistent with our results, Lin et al also showed that knockout of METTL3 in pre-osteoblastic MC3T3-E1 cells attenuated the level of ferroptosis [44]. However, Xu et al revealed that METTL3-mediated m 6 A modification of SLC7A11 mRNA was read by YTHDF1, which promoted the translation of SLC7A11 mRNA to inhibit lung adenocarcinoma cell ferroptosis [45]. The possible reason for this opposite scenario is that there are differences in the energy metabolism of tumor cells (aerobic glycolysis) and normal cells (mitochondrial oxidative phosphorylation) [46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our results, Lin et al also showed that knockout of METTL3 in pre-osteoblastic MC3T3-E1 cells attenuated the level of ferroptosis [44]. However, Xu et al revealed that METTL3-mediated m 6 A modification of SLC7A11 mRNA was read by YTHDF1, which promoted the translation of SLC7A11 mRNA to inhibit lung adenocarcinoma cell ferroptosis [45]. The possible reason for this opposite scenario is that there are differences in the energy metabolism of tumor cells (aerobic glycolysis) and normal cells (mitochondrial oxidative phosphorylation) [46].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the m 6 A methylated mRNAs may have different fates when recognized by different readers. For example, the mRNA of SLC7A11 is recognized by YTHDC2 to promote its degradation [32], while the recognition by YTHDF1 promotes its translation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that m 6 A modification enhances ferroptosis in stellate cells by stabilizing BECN1mRNA to trigger autophagy activation [ 16 ]. Other studies have found that METTL3-mediated m 6 A methylation can stabilize SLC7A11mRNA and accelerate translation, thereby inhibiting ferroptosis and accelerating the proliferation of lung cancer cells [ 7 ]. In this study, we also found that increased m 6 A methylation levels upregulated FUS expression and inhibited ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Erastin, a ferroptosis inducer, and second-generation antiandrogen RSL3 therapy phenomenally reduced CRPC growth and migration with no adverse effects [ 5 ]. OIP5-AS1 can regulate the expression of ferroptosis marker SLC7A11 through miR-128-3p, thus accelerating the progression of PRAD and ferroptosis resistance [ 7 ]. In addition, studies have found that flubendazole can induce P53 expression, downregulate ferroptosis markers SLC7A11 and GPX4 levels, and play an anti-CRPC proliferation and proapoptotic effect [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell ferroptosis, a novel form of programmed cell death. The highly expressed METTL3 in LUAD can promote LUAD cell proliferation and inhibit ferroptosis, and its molecular mechanism is that METTL3-mediated m6A modification enhances the stability of SLC7A11 mRNA and promotes its translation ( Xu et al, 2022 ). Metabolic reprogramming, known as the Warburg effect, is considered a key hallmark of cancer, including lung cancer.…”
Section: Part 2: the Role Of M6a Modification In Cancermentioning
confidence: 99%